Perlindungan Konsumen terhadap Penyalahgunaan Barcode dalam Pembelian BBM Bersubsidi menurut Fatwa DSN-MUI No. 110/DSN-MUI/IX/2017 - Tanjung, Aisyah Sabrina; Zahara, Fatimah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The misuse of barcode technology in the purchase of subsidized fuel (BBM) is still frequently observed, resulting in losses for consumers. This study aims to examine the protection of consumer rights according to the law in cases of barcode misuse in the purchase of subsidized fuel, based on DSN-MUI Fatwa No. 110/DSN-MUI/IX/2017. The research employs an empirical juridical method with a conceptual approach, in which the collected data were processed and analyzed using qualitative methods. The findings indicate various irregularities in the purchase of subsidized fuel, such as barcode forgery, duplicate barcode usage, and misuse of consumer data. The misuse of barcodes in the purchase of subsidized fuel not only violates positive law but also contravenes Sharia principles. This study emphasizes the importance of protecting consumer rights, including the right to obtain products and services fairly and in accordance with Sharia.